Leadership Style of Multinational Corporations: A brief review - Sukri, Al; Shasrini, Tessa (International Journal of Media and Communication Research, 2020)
While leadership is learned, the skills and knowledge processed by the leader can be influenced by his or hers attributes or traits such as beliefs, values, ethics and character, Knowledge and skills contribute directly to the process of leadership, while the other attributes give the leader certain characteristics that make him or her unique. The purpose of this study is to identify the Keys for Success in the Leadership of Multinational Corporations. Leadership is important for the design and development of organizational strategy and structure. Leadership styles differ and each leader selects a style best suited to his personality. The specific objective for this study is to determine the effectiveness of leadership traits that contributes to the success of Multinational corporations. This article reflect on case studies and example.